Gypsum seeding to prevent scale formation and improve separation efficiency - Chagwedera, Taona Malvin (Department of Chemical Engineering, 2022)
Eutectic freeze crystallization (EFC) is a novel separation technique that can be applied to treat brine solutions such as reverse osmosis retentates. These are often a mixture of different inorganic solutes. The treatment of calcium sulphate-rich brines using EFC often results in gypsum crystallization before any other species. This results in gypsum scaling on the cooled surfaces of the crystallizer, which is undesirable as it retards heat transfer rates and hence reducing the yield of other products. Gypsum crystallizes in small quantities compared to ice and mostly as fines because it is at lower concentrations. This also results in the entrapment of gypsum by the ice during gravity separation of the crystallization products. The aim of this study was to firstly investigate and understand gypsum crystallization and gypsum scaling in the presence of gypsum seeds. Secondly, it was to investigate the effect of gypsum seeding on gypsum separation efficiency. Synthetic brine solutions were used in this research because they allowed an in-depth understanding of the gypsum bulk crystallization process and scaling tendency without the complexity of industrial brines. Cooling crystallization experiments were conducted to investigate the effect of gypsum seeding on gypsum scaling, and EFC experiments were conducted to investigate the effect of gypsum seeding on gypsum separability from the ice. Gypsum seeding was effective in decreasing the mass of scale that formed on the heat transfer surface. Gypsum seeds improved gypsum crystallization kinetics in the bulk solution which resulted in an increase in the mass of gypsum product. Gypsum seeding marginally increased melted ice purity, although the proportion of gypsum which crystallized as fines in the suspension decreased significantly. This was because gypsum deported to the ice fraction mainly through mother liquor entrainment which was contrary to the expectation at the start of the research. The hypothesis was that gypsum reported to the ice fraction mainly through entrapment. It was recommended that the use of silica as a seed material to prevent gypsum scaling should be investigated in future studies. In addition, the treatment of calcium sulphate-rich brines using EFC should be done in stages with the first stage focusing on maximum gypsum removal using a residence time of 5 hours or more.